Automatic pollution sensing and control for vehicles using IoT technology. (2021) - Hepsiba, D.; Varalakshmi, L.M.; Suresh Kumar, M.; Subburaj, Jayasudha; Vijayakumar, P.; Sheeba Rani, S.
Abstract: The applications of vehicles are gradually increasing day by day. Simultaneously, vehicle pollution is also drastically increased. Due to improper maintenance and monitoring, the performances of the vehicles have been decreased. The different types of system and methods are available to detect the vehicle performance and pollution control. This paper is presented and provides an idea about pollution and vehicle control based on Internet of Things (IoT). The sensors, communication network, micro controller and server have been used for vehicle performance and their pollution control. The different vehicle parameters are monitored through IoT based system. The pollution experimental trail is conducted and compared with and without internet of things. The experimental investigations and their comparison have been reported with and without IoT system.